Constructions of female homoeroticism in early modern drama - Walen, Denise A. (Early modern cultural studies., 2005)
Constructions of Female Homoeroticism in Early Modern Drama explores textual representations of love and desire between female characters in a number of plays written between 1580 and 1660. The work argues that playwrights of late sixteenth- and early seventeenth-century England recognized and constructed richly diverse tropes of female homoerotic desire. This book analyzes a significant body of dramatic texts, many identified for the first time, that reveal the way playwrights conceived of desire between women, including Philaster, Hymen's Triumph, The Lover's Melancholy, The Doubtful Heir, A Christian Turn'd Turk, Orgula, and others.